Experimental investigation on ferritic stainless steel composite slabs. (1st November 2018) - Arrayago, I.; Ferrer, M.; Marimon, F.; Real, E.; Mirambell, E.
Highlights: Experimental programme on composite slabs with ferritic stainless steel trapezoidal deck is presented. Long span and short span slabs are tested. Parameters corresponding to m - k and Partial Connection Methods are determined. Results are compared to reference tests on galvanized steel for ULS and SLS. Abstract: Steel-concrete composite structures are well established in the construction of floors and roofing, being interesting solutions as steel decks act as formwork for relatively large spans and support the weight of the concrete and construction loads. However, the use of stainless steel decks in such structures has been very limited, although their mechanical properties, corrosion resistance, aesthetics and emissivity make them excellent for visually exposed composite floor slabs where the thermal capacity of the slab is mobilized as part of an energy saving strategy. This paper presents a comprehensive investigation on composite slabs with trapezoidal ferritic stainless steel decks in order to assess the performance of such structural members. Composite slabs made from EN1.4003 ferritic stainless steel and common C25/30 concrete were tested in two series of span lengths in order to determine the different parameters defining their ultimate longitudinal shear response. Reference tests on slabs with galvanized steel were also conducted with identical geometries and configurations. The m and k parameters used in the m - k Method and the design longitudinal shear strength τ u, Rd corresponding to the Partial Connection Method have been determined according to EN 1994-1-1:2004. Finally, the behaviour of these composite slabs was compared with the performance shown by the conducted reference slabs with galvanized steel deck in terms of Ultimate and Serviceability Limit States.